Comparative studies of silicon photomultipliers and traditional vacuum photomultiplier tubes - 石峰 吕军光 卢红 王焕玉 马宇蒨 胡涛 周莉 蔡啸 孙丽君 俞伯祥 方建 谢宇广 安正华 王志刚 高旻 李新乔 徐岩冰 王平 孙希磊 章爱武 薛镇 刘宏邦 王晓东 赵小芸 郑阳恒 孟祥承 王辉 (Chinese physics C, 2011)
Silicon photomultipliers （SiPMs） are a new generation of semiconductor-based photon counting devices with the merits of low weight, low power consumption and low voltage operation, promising to meet the needs of space particle physics experiments. In this paper, comparative studies of SiPMs and traditional vacuum photomultiplier tubes （PMTs） have been performed regarding the basic properties of dark currents, dark counts and excess noise factors. The intrinsic optical erosstalk effect of SiPMs was evaluated.